Evidence for non-communicable diseases: analysis of Cochrane reviews and randomised trials by World Bank classification. Issue 7 (6th July 2013) - Heneghan, C; Blacklock, C; Perera, R; Davis, R; Banerjee, A; Gill, P; Liew, S; Chamas, L; Hernandez, J; Mahtani, K; Hayward, G; Harrison, S; et al.
Abstract : Introduction: Prevalence of non-communicable diseases (NCDs) is increasing globally, with the greatest projected increases in low-income and middle-income countries. We sought to quantify the proportion of Cochrane evidence relating to NCDs derived from such countries. Methods: We searched the Cochrane database of systematic reviews for reviews relating to NCDs highlighted in the WHO NCD action plan (cardiovascular, cancers, diabetes and chronic respiratory diseases). We excluded reviews at the protocol stage and those that were repeated or had been withdrawn. For each review, two independent researchers extracted data relating to the country of the corresponding author and the number of trials and participants from countries, using the World Bank classification of gross national income per capita. Results: 797 reviews were analysed, with a reported total number of 12 340 trials and 10 937 306 participants. Of the corresponding authors 90% were from high-income countries (41% from the UK). Of the 746 reviews in which at least one trial had met the inclusion criteria, only 55% provided a summary of the country of included trials. Analysis of the 633 reviews in which country of trials could be established revealed that almost 90% of trials and over 80% of participants were from high-income countries. 438 (5%) trials including 1 145 013 (11.7%) participants were undertaken in low-middle income countries. We found that only 13 (0.15%) trials with 982 (0.01%) participants were undertaken in low-income countries. Other than the five Cochrane NCD corresponding authors from South Africa, only one other corresponding author was from Africa (Gambia). Discussion: The overwhelming body of evidence for NCDs pertains to high-income countries, with only a small number of review authors based in low-income settings. As a consequence, there is an urgent need for research infrastructure and funding for the undertaking of high-quality trials in this area.